Efektifitas Konseling Behavioral Teknik Modelling Dengan Setting Lesson Study Untuk Meningkatkan Self Succorance Siswa Kelas VII.3 SMP Lab Undiksha Singaraja - resti, indah (Department of Guidance and Counseling, FIP, Undiksha, 2018)
The purpose of this study was to determine the effectiveness of behavioral counseling modeling techniques with lesson study settings to improve self-coursework in students of class VII 3 of SMP Undiksha Singaraja Lab. Research This experiment used a pretest-posttest control group design. The research population is the seventh grade students of the Undiksha Lab Singaraja Buleleng Bali. The research research data was collected by Self Succorance inventory. The data of this study were analyzed with a differential t-test and continued in Cohen to calculate the effectiveness of using the JASP0.10.0.0 program for Windows for Windows. The results of the analysis showed 1) the value of p - 0.001, significant at 0.001> 0.05 2) Effect size of 2.401 categorized as high. This means that there is a significant difference in the value of students who are given treatment behavioral counseling modeling techniques. Students given treatment were higher in self-efficacy compared to students without treatment. Become behavioral counseling with effective modeling techniques to improve self-learning.